IMPROVING CASH ACCOUNTING IN ENTERPRISES BASED ON INTERNATIONAL STANDARDS (International Conference on Modern Science and Scientific Studies, 2025)
Cash funds are considered vital economic resources in ensuring the financial stability of an enterprise. This article analyzes the role and main functions of cash in business operations, and how proper management of these funds contributes to economic efficiency. It elaborates on the classification of cash assets and the importance of maintaining proper accounting practices. Particular focus is given to transactions related to settlement and foreign currency accounts held in banks, supported by practical examples. The article also explores the accounting of other cash equivalents, such as cash on hand, card transactions, and related financial activities. Through this analysis, the article emphasizes the significance of accurate and transparent cash accounting in strengthening a company's financial position.